Role of Libraries in Fifth Industrial Revolutions: Prospects and Challenges - Abid Hussain (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose - The Industrial Revolution 5.0 (IR5.0), characterized by its human-centric approach, is anticipated to transform global industries both socially and economically. Despite its potential, little is known about research trends within specific sectors, particularly libraries, which have historically served as agents of change during major technological shifts. However, the role of libraries in IR5.0 remains underexplored. This study aims to investigate various applications of IR5.0 and assess its implications for libraries and librarians. Methods – This study employs a qualitative research design, utilizing content analysis and a literature review approach. A literature review was conducted across various databases such as Google Scholar, Taylor & Francis Journals, ScienceDirect, SpringerLink and ProQuest. Thirty studies on IR5.0 were analyzed, with a particular focus on those addressing library applications, to provide a foundation for future research in this area. Findings – The literature review reveals that European nations have initiated discussions and applications of IR5.0 across different sectors. The most influential research originates from developed countries such as the United States, Sweden, Australia, and Germany, where libraries are actively exploring IR5.0's potential. In contrast, libraries in developing nations tend to follow the lead of these advanced countries. The findings also suggest that librarians with limited technical skills and training may face challenges in adopting IR5.0. Additionally, potential barriers to implementing IR5.0 in libraries include the costs of hardware and software, data security issues, and the need for technically proficient staff.Research implications – This study is based on a review of existing literature and does not include primary empirical research. As a result, the findings may differ from those in experimental studies. Future empirical research on IR5.0 is necessary to explore its practical implications. The study offers preliminary insights that may guide scholars in understanding both the benefits and challenges of IR5.0, given its limited large-scale implementation to date.Originality – This research contributes foundational knowledge for theoretical and practical discussions surrounding IR5.0, specifically within the context of libraries and librarianship. It highlights the scope of IR5.0 in libraries and underscores the need for further studies employing interviews, case studies, and surveys to deepen understanding of its practical applications.